Chitosan/luminol/AgNPs nanocomposite for electrochemiluminescent determination of prostate?specifc antigen - Nasrollahpour, Hassan; Khalilzadeh, Balal; Naseri, Abdolhossein; Mamaghani, Shahab; Isildak, Ibrahim; Rashidi, Mohammad-Reza (SPRINGER WIEN, 2023)
A green, environmentally friendly protocol was developed for ultrasensitive and highly specific recognition of prostate-specific antigen (PSA) based on the ECL effect of luminol supported by chitosan-silver nanoparticles (CS/AgNPs) nanocomposites. The transducing surface was fabricated through two consecutive electrodeposition steps of gold nanoparticles (AuNPs) and chitosan (CS)-AgNPs-luminol electrochemiluminophore onto the glassy carbon electrode. In addition to an appropriate desirable biocompatibility, the electrochemical synthesis presents low-cost preparation and ultrafast determination opportunity. AgNPs play a linking role to attach luminol, as an ECL agent to the CS support via donor-acceptor bonds between Ag atoms with NH groups of luminol and CS. Also, AgNPs can amplify the ECL intensity as a consequence of their excellent specific surface area and conductivity. To enhance the performance of the nanobiosensor, AuNPs were also used due to their high-specific surface area and excellent affinity toward amine groups of CS. Based on this high-performance analysis strategy, ultrasensitive screening of PSA was attained with a desirable limit of detection of 0.6 ng mL(-1) and a broad linear range between 1 pg mL(-1) and 10 ng.mL(-1) (R-2=0.994). Approximately, the same results were recorded for the analysis of the unprocessed serum samples of patients with prostate cancer at different stages. This research provided significant insight into electrografting methods to construct ECL transducers for clinical monitoring of PSA and other tumor biomarkers in the clinical setting.
Keywords: Electrochemiluminescnece; Prostate-specific antigen; Gold nanoparticles; Nanobiocomposite; Biosensor; Electrodeposition; BIOSENSORS; STRATEGY; Chemistry